Effect of Waterlogging-Induced Autophagy on Programmed Cell Death in Arabidopsis Roots - Guan, Bin; Lin, Ze; Liu, Dongcheng; Li, Chengyang; Zhou, Zhuqing; Mei, Fangzhu; Li, Jiwei; Deng, Xiangyi (Frontiers in Plant Science, 2019)
Autophagy, a highly conserved process in eukaryotes that involves vacuolar degradation of intracellular components and decomposition of damaged or toxic constituents, is induced by endogenous reactive oxygen species (ROS) accumulation, endoplasmic reticulum stress and other factors. In plants, the role of autophagy in the induction of programmed cell death (PCD) is still unclear. Here, we show that ROS contribute to the regulation of PCD during waterlogging (which results in oxygen depletion) via autophagy. In wild type roots, waterlogging induces the transcription of hypoxia-responsive genes and respiratory burst oxidase homolog (RBOH)-mediated ROS production. It also altered the transcription level of alternative oxidase1a and the activity level of antioxidant enzymes. Moreover, waterlogging increased the transcription levels of autophagy-related (ATG) genes and the number of autophagosomes. Autophagy first occurred in the root stele, and then autophagosomes appeared at other locations in the root. In rboh mutants, upregulation of autophagosomes was less pronounced than in the wild type upon waterlogging. However, the accumulation of ROS and the level of cell death in the roots of atg mutants were higher than those in the wild type after waterlogging. In conclusion, our results suggest that autophagy induced in Arabidopsis roots during waterlogging has an attenuating effect on PCD in the roots.